Peningkatan kualitas standar layanan terhadap kepuasan nasabah di bank syariah - Rosyada, Amrina (Maliki Interdisciplinary Journal, 2025)
This study aims to further examine the factors that affect customer satisfaction in an effort to increase customer satisfaction in Sharia Banks. In a competitive banking industry, customer satisfaction is the main indicator of service success and determines long-term loyalty. This research uses a descriptive qualitative method with a literature study approach, which involves the analysis of various literature sources, scientific journals, and relevant theories. The results of the study show that factors such as speed and efficiency of service, product innovation, human resource competence, and the use of technology such as internet banking greatly affect the level of customer satisfaction. The SERVQUAL model is used as a measuring tool in assessing the five main dimensions of service quality, namely tangible, responsiveness, reliability, assurance, and empathy.